Technological modernity excludes men and women from economic activities. It incorporates more the woman in the city than in rural areas - Rossini, Rosa Ester (GEOUSP Espaço e Tempo (Online), 2002)
The technological modernization in process has created huge transformations in the labor world. In Brazil, with the gradual shift from formal jobs to flexible occupation, the rise of outsourcing and the informal sector, women are pushed away from the formal labor market. The increase of female work in the 1990s (induced by dropping fertility), spreading urbanization, better female education levels, and several others factors, have not avoided the exclusion of women from labor market. While female activities are predominantly urban, agriculture is becoming essentially dominated by men. This happens due to the fact that agriculture has become highly mechanized and women do not operate sophisticated machines